Economic Empowerment of Pesantren Through Independent Entrepreneurial Business (A Study of Daarul Ukhuwwah Putra Islamic Boarding School In Malang) - Nashir, Muhammad Kautsar; Noor, Iswan (Islamic Economics and finance in Focus, 2025)
The purpose of this study is to analyze and describe the economic empowerment process carried out by Daarul Ukhuwwah Putra Islamic Boarding School through independent business, supporting and inhibiting factors in the economic empowerment of pesantren through independent business, and the impact of independent business on improving the welfare of pesantren, students, and the surrounding community. The method used in this research is descriptive qualitative with a case study approach. Data collection techniques were carried out by interview, observation, and documentation which were analyzed with Miles and Huberman's interaction model. The results of this study indicate that Daarul Ukhuwwah Putra Islamic Boarding School in Malang implements economic empowerment through independent business ventures by establishing business units such as maksof, building shops, and canteens, which involve santri in the management and provision of practice-based entrepreneurship. Supporting factors for economic empowerment include the support of the pesantren leadership, the availability of potential human resources, and cooperation with the surrounding community. However, there are obstacles such as low understanding of business management, less than optimal dependence on technology, and lack of discipline in applying SOPs. This independent business has a positive impact, with profits used for the construction of pesantren facilities, as well as providing entrepreneurial experience and skills for santri. The impact is also felt by the surrounding community who are involved in providing goods and services, which increases their economic income. Overall, this empowerment not only improves the welfare of pesantren and santri, but also strengthens social networks and improves the quality of life of the surrounding community.